1999
DOI: 10.1038/16711
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of human TRPC6 and TRPC3 channels by diacylglycerol

Abstract: Eukaryotic cells respond to many hormones and neurotransmitters with increased activity of the enzyme phospholipase C and a subsequent rise in the concentration of intracellular free calcium ([Ca2+]i). The increase in [Ca2+]i occurs as a result of the release of Ca2+ from intracellular stores and an influx of Ca2+ through the plasma membrane; this influx of Ca2+ may or may not be store-dependent. Drosophila transient receptor potential (TRP) proteins and some mammalian homologues (TRPC proteins) are thought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
1,308
7
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,378 publications
(1,381 citation statements)
references
References 25 publications
63
1,308
7
3
Order By: Relevance
“…The precise mechanism between PKC activation and TRPC3 opening remains however to be firmly established, but our data suggested that Src is, at least partially, involved in this process. Considering that the inhibition of the Ca 2+ entry varied between about 40 and 60% upon src inhibition or siRNA treatment against PKC , it is possible that for a part, TRPC3 is also getting directly activated by DAG, like it was already reported [15,63,64]. This point, however, remains to be further investigated.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The precise mechanism between PKC activation and TRPC3 opening remains however to be firmly established, but our data suggested that Src is, at least partially, involved in this process. Considering that the inhibition of the Ca 2+ entry varied between about 40 and 60% upon src inhibition or siRNA treatment against PKC , it is possible that for a part, TRPC3 is also getting directly activated by DAG, like it was already reported [15,63,64]. This point, however, remains to be further investigated.…”
Section: Discussionmentioning
confidence: 81%
“…When exogenously expressed some TRPC channels displayed SOCE activity [12][13][14]. However, numerous studies also demonstrated that TRPC channels did not operate as SOCE channels, but rather are gated by second messengers like Ca 2+ or diacylglycerol (DAG; [15][16][17]). Hence, the involvement of TRPC channels in the SOCE mechanism is a controversial issue, and appears to dependent on the cell types investigated, and importantly on the expression level of the TRPC [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Because TRPC6 channels can be activated by diacylglycerol (DAG) [20], we used OAG, a membranepermeable analogue of DAG, to test Ca 2+ inflow in cells.…”
Section: Trpc6-mediated Calcium Entrymentioning
confidence: 99%
“…In our studies, no effect of TGF-on the fetal calf serum-, EGF-, and PMA-induced activation of PLD was observed. Effects of TGF-1 on the PC-and PIPs-derived DAG formation Altered PLD activity could influence the level of intracellular second messenger DAG, which is formed through PA phosphatase-catalyzed hydrolysis of PA. DAG plays an important role in cellular growth and other functions, which acts as a physiological activator for some PKC isoforms [26] and has been shown to be a direct Ca 2+ ion channel regulator [27]. Though it has been reported that PC-PLC are involved in the TGF-1 -mediated signaling or growth inhibition [28], [29], the effects of TGF-on the phospholipase activity and the DAG production has not been determined.…”
Section: Tgf-β 1 Induces the Activation Of Pld Activity In Mv1lu MDCmentioning
confidence: 99%